Anticoagulation after typical atrial flutter ablation: Systematic review and meta‐analysis. Issue 10 (1st September 2021) - Nunes‐Ferreira, Afonso; Alves, Mariana; Lima da Silva, Gustavo; Cortez‐Dias, Nuno; de Sousa, João; Pinto, Fausto J; Caldeira, Daniel
Abstract: Background: Cavotricuspid isthmus (CTI) ablation in typical atrial flutter (AFL) restores sinus rhythm in 95% of patients, which may lead to the discontinuation of oral anticoagulation during follow‐up. Therefore, we aimed to systematically review the clinical impact of oral anticoagulation in the incidence of thromboembolic events (TE) after typical AFL ablation. Methods: We searched for controlled studies evaluating the impact of anticoagulation in the incidence of TE in patients submitted to AFL ablation in MEDLINE, CENTRAL, PsycINFO database (June/2021). The primary outcome was TE events (ischemic stroke or systemic embolism). A meta‐analysis was performed deriving risk ratios (RR) and 95% confidence intervals (CI). Statistical heterogeneity was measured through I 2 metric. The confidence in the evidence was appraised with Grading of Recommendations Assessment, Development and Evaluation (GRADE) framework. Results: Eight observational studies with 4870 patients were included. TE events were not significantly reduced (RR 1.18, 95% CI 0.59–2.36; n = 4870; GRADE very low). A meta‐regression showed that for each 10% increase in the prevalence of previous AF in the studied population, anticoagulation reduced TE risk in 32%. There were no significant differences regarding bleeding events (RR 2.16, 95% CI 0.43–10.97, I 2 = 0%; GRADE low), but there was a lower all‐cause mortality (RR 0.24, 95% CI 0.17–0.32, GRADE low). Conclusion: The best available evidence lacks robustness and the data did not definitely associate anticoagulation after typical AFL ablation with reduced TE.